Model Pembinaan Menghafal Al-Qur'an Mahasantri Pondok Muhammadiyah Hajjah Nuriyah Shabran dalam Meningkatkan Hafalan Al-Qur'an Tahun Akademik 2014/2015 - Mustawa, Drs. Zaenal Abidin, M.Pd, Dr. Mutohharun Jinan, M.Ag (2016)
Learn and memorize the Koran is one of the cottage program Hajjah Nuriyah Shabran Muhammadiyah Muhammadiyah University of Surakarta (UMS Shabran cottage). But in reality does little mahasantri less concerned or were reluctant to learn and memorize the Koran. To achieve all the coaching in the memorization of the Koran is needed for what is expected to be achieved well. Therefore, the subject matter of this discussion is how the coaching model memorize the Koran and what methods are applied in improving memorization of the Qur'an mahasantri cottage Muhammadiyah Hajjah Nuriyah Shabran year 2014/2015? The purpose of this study was to describe the coaching model memorizing the Qur'an and to describe methods of memorization of the Qur'an are applied in improving memorization of the Qur'an mahasantri cottage Muhammadiyah Hajjah Nuriyah Shabran year 2014/2015. The benefits of this research, namely (1) the theoretical benefits, is expected to contribute positively to lodge Muhammadiyah Hajjah Nuriyah Shabran in coaching mahasantri to keep discipline in memorizing al-aqur'an; (2) the benefits fraktis, is expected to provide input for the board mahasantri cottage in coaching and as a material consideration in the use and development of memorization method that mahasantri always disciplined in memorizing the Koran. This research is classified research field. Sources of data in this study is a builder, caretaker cottage and lodge mahasantri Muhammadiyah Hajjah Nuriyah Shabran. In collecting data using interviews, observation, and documentation. While the method of data analysis using qualitative descriptions. The analysis is inductive analysis. Based on the analysis of research data, it can be deduced that the coaching model memorizing the Koran mahasantri cottage Muhammadiyah Hajjah Nuriyah Shabran in improving the memorization of the Koran academic year 2014/2015 the model halaqah, mentoring models, models of reward and punishment, the model of habituation and models muballigh hijjrah. While the method of memorization of the Koran mahasantri cottage Muhammadiyah Hajjah Nuriyah Shabran in improving the memorization of the Koran academic year 2014/2015 is the method jama'i, sima'i, Wahdah, in pairs, and methods muraja'ah.